A formação do psicólogo e o uso crítico de tecnologias de comunicação - Cortez, Bruno Oliveira (Brasil, 2025)
Historically, psychology education has been a point of contention for certain sectors of society. These tensions, coupled with the COVID-19 pandemic in 2020 and the onset of emergency remote teaching (ERT), led to the creation of new National Curriculum Guidelines (NCG) for psychology programs in 2023. These guidelines emphasize the use of information and communication technologies (ICT) to encourage students to critically reflect on their application. This study aims to explore the use of ICT in undergraduate psychology programs through a narrative review. The research was conducted using the platforms Scientific Electronic Library Online (SciELO), Virtual Health Library (BVS), and Google Scholar, resulting in the selection of nine studies that were analyzed through Content Analysis and contextualized within Paulo Freire's concept of dialogicity. The teaching experiences examined were linked to ERT and highlighted opportunities for innovation. However, the primary challenge lies in overcoming the commodification of education by advocating for public policies that improve student access to electronic devices, provide teacher training programs, and establish proper regulations for the use of these tools. Even so, it is recommended that ICT be integrated into in-person psychology education, as they help bridge the gap between students and professional practice while offering greater flexibility for educators.